Situational Leadership Leadership Maturity: Managing People to Perform and Building Commitments - bestri, Rafikah; Hadiyanto, Hadiyanto; Al Kadri, Hanif; Yahya, Yahya (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
Situational Leadership focuses on an individual's ability to identify and hen select work team strategies that, in their opinion, are most effective when pplied to each unique situation or task. Hersey and Balanchard also stated in their book Edgar H. Schein stated that a successful manager must have a good diagnostician who can assess the patient's emotional state. If a person's behavior and characteristics vary greatly, then he or she must have a high level of sensitivity and diagnostic ability in order to recognize and understand the behavior in question. But even with strong diagnostic abilities, managers frequently lack effectiveness unless they can modify their management approach to better suit the demands of their surroundings. Like Hersey and Blanchar, heads of state must have the personal integrity and skills necessary to adapt to situations. If the needs and motive background are different, then it is necessary to do it in a different way. Situational emulation is based on the following: The degree of relationship behaviors (or socio-emotional support) and task behaviors (or guidance and direction) that the leadership provides. the degree of obedience participants saw in completing particular duties, obligations, or objectives. The influence of situational leadership is felt in the team leader's interactions with team members. Participant safety is paramount in every situation. Not only because they individually like and respect the leader, but also because as a group they are very aware of the personal power that the leader has. The goal of this study is to ascertain how situational leadership is applied at the Branch Office of the Cabang Dinas Pendidikan Wilayah VIII Mentawai Islands Regency to motivate employees to work and foster a work-commitment culture. This study uses a case study as its foundation. In this study, methods for gathering data included interviewing, documenting, and participatory observation. Utilizing source triangulation techniques, data was processed. The study's conclusions indicate that 1) The maturity of members is the basis for leaders in taking managerial action and decision making. 2) The maturity of leaders in leading also influences the maturity of members. 3) Mature leaders are able to manage the maturity of their members so that they have good performance, 4) Mature leaders are also able to build the maturity of their members so that they have strong work commitment.